2021
DOI: 10.3390/ani11113139
|View full text |Cite
|
Sign up to set email alerts
|

High Seroprevalence of Toxoplasma gondii in Slovenian Wild Boars (Sus scrofa)

Abstract: Toxoplasma gondii is a zoonotic parasite of great public health concern. Wild boars could be considered an emerging source of toxoplasmosis in humans due to the popularity of venison and their increasing population. The aim of this study was to determine the seroprevalence of T. gondii in the Slovenian wild boar population and evaluate risk factors for human infection. Of 353 samples, 62% were positive for T. gondii using ELISA tests. This is the highest T. gondii seroprevalence reported to date in wild boar w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Indeed, several studies showed that age is a relevant risk factor affecting seroprevalences in pigs, due to the typical postnatal infection that occurs in this species [14]. This difference was also reported in wild boars, where it was shown that being T. gondiipositive increases with age, with a 2.66-fold higher risk in 2-3-year-old pigs compared to that of 1-2-year-old pigs [15]. Thus, our results are likely to suggest that the farming conditions of the private pig farming described herein, such as the low number of animals, housing in separate boxes and limited rearing period, could mitigate parasite circulation in pigs.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, several studies showed that age is a relevant risk factor affecting seroprevalences in pigs, due to the typical postnatal infection that occurs in this species [14]. This difference was also reported in wild boars, where it was shown that being T. gondiipositive increases with age, with a 2.66-fold higher risk in 2-3-year-old pigs compared to that of 1-2-year-old pigs [15]. Thus, our results are likely to suggest that the farming conditions of the private pig farming described herein, such as the low number of animals, housing in separate boxes and limited rearing period, could mitigate parasite circulation in pigs.…”
Section: Discussionmentioning
confidence: 65%
“…At a European level, the prevalence of Toxoplasma in wild boar varies depending on the region and the technique, ranging from 5.2% in Greece [ 53 ] to 62% in Slovenia [ 35 ]. The lack of a perfect technique (with 100% specificity and 100% sensitivity) for the detection of T. gondii is well-known [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Toxoplasma infection in wild boar is influenced by factors such as the age and sex of the animals as well as the season and weather conditions [ 29 , 30 ]. Prevalence varies in different European countries: 40% (range 32–59%) in the Czech Republic [ 31 ]; 48% in Poland [ 32 ]; 29% (range 5–45%) in Sweden [ 33 ]; 16.8% in France [ 34 ]; 62% in Slovenia [ 35 ]; 35% in Switzerland [ 36 ]; and 15.5% in Italy [ 37 ]. In Spain, prevalence also varies between different areas: 14.1% in the Valencian Community [ 30 ]; 39% in Doñana National Park [ 29 ]; 19.4% in Andalusia [ 38 ]; 23.88% in the Extremadura Region and 20.8% in the Sierras de Cazorla, Segura, and Las Villas Natural Park [ 39 ]; and 51.16% in Sierra Morena [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is distributed all around the world (Woyesa et al,2021), Toxoplasma gondii has been isolated from a variety of geographical regions (Yang et al,2021). According to estimates, this parasite threatens one-third of the world's population (Bandelj et al,2021). The parasite which is common in both humans and animals, causes the disease depending on where they reside, 15 to 85 percent of the human population is asymptomatically infected (Mose et al,2020).…”
Section: Introductionmentioning
confidence: 99%